2020
DOI: 10.1038/s41598-020-74700-x
|View full text |Cite
|
Sign up to set email alerts
|

Cell shape regulates subcellular organelle location to control early Ca2+ signal dynamics in vascular smooth muscle cells

Abstract: The shape of the cell is connected to its function; however, we do not fully understand underlying mechanisms by which global shape regulates a cell’s functional capabilities. Using theory, experiments and simulation, we investigated how physiologically relevant cell shape changes affect subcellular organization, and consequently intracellular signaling, to control information flow needed for phenotypic function. Vascular smooth muscle cells going from a proliferative and motile circular shape to a contractile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 90 publications
0
14
0
Order By: Relevance
“…More recently, we used a deterministic reaction-diffusion model to investigate dendritic spine morphology and ultrastructure and found that dendritic spine volume-to-surface-area ratios and the presence of spine apparatus (SpApp) modulate calcium levels ( Bell et al, 2019 ). As we have shown before, the natural length scale that emerges for reaction-diffusion systems with boundary conditions that have influx and efflux rates is the volume-to-surface-area ratio ( Calizo et al, 2020 ; Cugno et al, 2019 ). What remains unclear is whether the trends from dimensional analysis of deterministic models continue to hold despite the stochastic nature of calcium influx and efflux across the wide range of spine shapes.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…More recently, we used a deterministic reaction-diffusion model to investigate dendritic spine morphology and ultrastructure and found that dendritic spine volume-to-surface-area ratios and the presence of spine apparatus (SpApp) modulate calcium levels ( Bell et al, 2019 ). As we have shown before, the natural length scale that emerges for reaction-diffusion systems with boundary conditions that have influx and efflux rates is the volume-to-surface-area ratio ( Calizo et al, 2020 ; Cugno et al, 2019 ). What remains unclear is whether the trends from dimensional analysis of deterministic models continue to hold despite the stochastic nature of calcium influx and efflux across the wide range of spine shapes.…”
Section: Introductionmentioning
confidence: 81%
“…Dendritic spines have characteristic sizes and shapes that dynamically change over time in response to stimulus and are associated with their function and synaptic plasticity ( Bourne and Harris, 2008 ; Holthoff et al, 2002 ). Just as whole-cell shape is known to influence signaling dynamics ( Calizo et al, 2020 ; Neves et al, 2008 ; Rangamani et al, 2013 ; Héja et al, 2021 ; Bell and Rangamani, 2021 ; Scott et al, 2021 ), studies have specifically probed the interplay between calcium dynamics and dendritic spine morphology ( Bell et al, 2019 ; Cugno et al, 2019 ; Yuste et al, 2000 ; Bartol et al, 2015 ). Because of the historical significance of dendritic spines as electrical subcompartments, the morphology of the spine neck has been implicated in regulating calcium signaling, and longer spine necks were found to decouple spine-dendrite calcium signaling ( Volfovsky et al, 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, we used a deterministic reaction-diffusion model to investigate dendritic spine morphology and ultrastructure, and found that dendritic spine volume-to-surface area ratios and the presence of spine apparatus modulate calcium levels ( 35 ). As we have shown before, the natural lengthscale that emerges for reaction-diffusion systems with boundary conditions that have influx and efflux rates is the volume-to-surface area ratio ( 29, 36 ). What remains unclear is whether the trends from dimensional analysis of deterministic models continue to hold despite the stochastic nature of calcium influx and efflux across the wide range of spine shapes.…”
Section: Introductionmentioning
confidence: 79%
“…Dendritic spines have characteristic sizes and shapes that dynamically change over time in response to stimulus, and are associated with their function and synaptic plasticity ( 27, 28 ). Just as whole cell shape is known to influence signaling dynamics ( 2934 ), studies have specifically probed the interplay between calcium dynamics and dendritic spine morphology ( 7, 3537 ). Due to the historical significance of dendritic spines as electrical subcompartments, the morphology of the spine neck has been implicated in regulating calcium signaling and longer spine necks were found to decouple spine-dendrite calcium signaling ( 38 ).…”
Section: Introductionmentioning
confidence: 99%
“…When vascular damage is repaired, vascular remodeling occurs under altered hemodynamics, or in disease states, VSMCs dedifferentiate into a synthetic phenotype that secretes exosomes, a process known as phenotype switching ( 8 ). Several lesions of the vascular system have been associated with phenotypic conversion of VSMC, such as AS, restenosis, and VC ( 35 ). EVs produced by VSMC under physiological conditions do not contain calcium phosphate crystals and also transport calcification inhibitory proteins such as vitamin k-dependent MGP and fetuin-A ( 28 ).…”
Section: Extracellular Vesiclesmentioning
confidence: 99%